"Whatever it takes": An Empirical Assessment of the Value of Policy Actions in Banking. (17th December 2015) - Fiordelisi, Franco; Ricci, Ornella
Abstract : What types of policy intervention had a greater impact during the financial crisis? By using a detailed dataset of worldwide policy, we answer this question focusing on Global Systemically Important banks (G-SIBs), looking both to stock returns and Credit Default Swap (CDS) spreads reactions. As robustness checks, we also analyze a control sample of 31 large Non-Financial Companies (NFCs). Overall, we show that different policy interventions from governments and central banks have produced diverse market reactions: investors generally appreciate monetary policy interventions for G-SIBs (but not for NFCs) and do not welcome bank failures and bailouts (for both G-SIBs and NCFs).